2021
DOI: 10.1111/1440-1681.13536
|View full text |Cite
|
Sign up to set email alerts
|

Moderate endurance training reduced hepatic tumourigenesis associated with lower lactate overload compared to high‐intensity interval training

Abstract: The anti‐tumour effects of exercise are still poorly understood. In recent years, high‐intensity interval exercise has been recognised as one of the best choices for better health. However, high‐intensity interval exercise induces lactate production in muscles and elevates blood lactic acid levels, and the resulting acidic microenvironment may promote tumour progression. Therefore, it is important to compare the anti‐tumour effects of different types of exercise. Objective In this study, we aimed to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…hepatocellular carcinoma animal model [39]. Nevertheless, another study demonstrated that the expression level in liver tissue increased after exercise in mice fed a high-fat diet [43].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…hepatocellular carcinoma animal model [39]. Nevertheless, another study demonstrated that the expression level in liver tissue increased after exercise in mice fed a high-fat diet [43].…”
Section: Plos Onementioning
confidence: 99%
“…The B cell receptor signaling pathway is enriched in the placenta tissue of pregnant women after recreational physical activity [38]. CD95 + B cells do not show significant changes in acute exercise in the bloodstream of adolescents or adults [39].…”
Section: Plos Onementioning
confidence: 99%
“…Again, endurance training decreased tumor incidence and size as compared to HIIT. There were no significant differences in the mRNA levels of key gluconeogenesis enzymes [ 62 ].…”
Section: Role Of Physical Activity In Hccmentioning
confidence: 99%